2021
DOI: 10.3791/62591
|View full text |Cite
|
Sign up to set email alerts
|

Microinjection Method for <em>Anopheles gambiae</em> Embryos

Abstract: Embryo microinjection techniques are essential for many molecular and genetic studies of insect species. They provide a means to introduce exogenous DNA fragments encoding genes of interest as well as favorable traits into the insect germline in a stable and heritable manner. The resulting transgenic strains can be studied for phenotypic changes resulting from the expression of the integrated DNA to answer basic questions or used in practical applications. Although the technology is straightforward, it require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…In this study we have developed a robust and effective procedure for generating knock-out mutants in D. pulex . The microinjection procedures in model organisms such as Drosophila (Ringrose 2009), Caenorhabditis elegans (Evans 2006), Anopheles mosquitoes (Carballar-Lejarazú et al 2021) inspired us to develop optimized fabrication for injection needles with upgraded glass capillary (i.e., aluminosilicate) and repurpose a flipped small Petri dish as the injection stage for Daphnia embryos. We directly inject RNPs instead of plasmids encoding Cas9/Cas12 and guide RNAs because RNPs can result in mutations at a much greater efficiency than injecting plasmids or mRNA encoding Cas enzymes (Kim et al 2014; Hendel et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In this study we have developed a robust and effective procedure for generating knock-out mutants in D. pulex . The microinjection procedures in model organisms such as Drosophila (Ringrose 2009), Caenorhabditis elegans (Evans 2006), Anopheles mosquitoes (Carballar-Lejarazú et al 2021) inspired us to develop optimized fabrication for injection needles with upgraded glass capillary (i.e., aluminosilicate) and repurpose a flipped small Petri dish as the injection stage for Daphnia embryos. We directly inject RNPs instead of plasmids encoding Cas9/Cas12 and guide RNAs because RNPs can result in mutations at a much greater efficiency than injecting plasmids or mRNA encoding Cas enzymes (Kim et al 2014; Hendel et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Functional genomics studies of mosquito vectors are crucial for understanding their physiological behavior, pathogen transmission, and evolution, and for providing essential molecular targets for genetic control (Severson & Behura, 2011; Ruzzante et al ., 2019; Alphey, 2014; HONG et al ., 2022). The main methods involve CRISPR-Cas9 gene editing via embryo microinjection (2016; Criscione et al ., 2015; Kistler et al ., 2015); however, technical barriers, including oviposition types, injection timing, training, expensive equipment, and specific injection protocols for different mosquito species (Criscione et al ., 2015; Au-Carballar-Lejarazú et al ., 2021), represent difficulties for laboratories studying non-model mosquitoes or lacking the required expertise and facilities for microinjection. The Receptor-Mediated Ovary Transduction of Cargo (ReMOT) method has been employed for germline-level gene editing in some model mosquitoes, involving injection of a Cas9/gRNA complex fused with a P2C ovarian-targeting peptide into adult female mosquitoes (Chaverra-Rodriguez et al ., 2018; Macias et al ., 2020; Li et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…
Dear editor,Functional genomics studies of mosquito vectors are crucial for understanding their physiological behavior, pathogen transmission, and evolution, and for providing essential molecular targets for genetic control (Severson & Behura, 2011;Alphey, 2014;Ruzzante et al, 2019;Hong et al, 2022). The main methods involve clustered regularly interspaced palindromic repeats (CRISPR) / CRISPR-associated protein 9 (Cas9) gene editing via embryo microinjection (Criscione et al, 2015;Kistler et al, 2015); however, technical barriers, including oviposition types, injection timing, training, expensive equipment, and specific injection protocols for different mosquito species (Criscione et al, 2015;Carballar-Lejarazú et al, 2021), represent difficulties for laboratories studying non-model mosquitoes or lacking the required expertise and facilities for microinjection. The Receptor-Mediated Ovary Transduction of Cargo (ReMOT) method has been employed for germline-level gene editing in some model mosquitoes, involving injection of a Cas9/genomic RNA (gRNA) complex fused with a P2C (a 41-amino acid peptide segment located in the N-terminal region of Drosophila melanogaster yolk protein 1) ovarian-targeting peptide into adult female mosquitoes (
…”
mentioning
confidence: 99%
“…We hypothesize that this stage signifies an absorption peak of ovarian cells via receptormediated endocytosis (Nicholson, 1921;Izumi et al, 1994;Sappington et al, 1995). Studies in other species found that the highest editing efficiency was achieved by injecting P2C-ribonucleoprotein (RNP) complexes during vitellogenesis (Chaverra-Rodriguez et al, 2018;Macias et al, 2020;Li et al, 2021;Shirai et al, 2022). We therefore hypothesized that injection at 20 h PBF might improve the transportation and accumulation of P2C-RNP complexes in the eggs, resulting in higher editing efficiency.…”
mentioning
confidence: 99%